High-entropy alloy nitride coating, preparation method thereof and wear-resistant part

By using AlTiVCrMoSiN high-entropy alloy nitride coating and combined with cathode arc ion coating, the problem of difficult to achieve high hardness, high elastic modulus and high wear resistance at the same time is solved, and efficient surface modification and performance improvement is achieved.

CN119663180APending Publication Date: 2025-03-21GUANGDONG INST OF NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411862990.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing high-entropy alloy nitride coatings are difficult to achieve high hardness, high elastic modulus and high wear resistance in the same coating, limiting their wide application in the high-end field.

Method used

AlTiVCrMoSiN high-entropy alloy is used as the coating material, and a high-entropy alloy nitride coating is deposited on the substrate surface by cathode arc ion coating method to form a high-entropy alloy nitride coating, and the element content and deposition parameters are adjusted to achieve dense and uniform structure and high hardness.

Benefits of technology

The ratio of high hardness to high elastic modulus (H/E) is achieved, which reduces the resistance to external impact and microcracks, improves the bonding force and stability between the coating and the substrate, and significantly improves the wear resistance and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663180A_ABST
    Figure CN119663180A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy alloy nitride coating, a preparation method of the high-entropy alloy nitride coating and a wear-resistant part, the coating is an AlTiVCrMoSiN high-entropy alloy nitride coating, and in corresponding preparation raw materials, the element content of Al ranges from 10% to 30%, the element content of Ti ranges from 10% to 30%, the element content of V ranges from 10% to 30%, and the element content of Cr ranges from 10% to 30%. The element content of Mo ranges from 5% to 25%, and the element content of Si ranges from 1% to 10%. The coating has a compact and uniform feature-free structure, and has excellent mechanical properties, high elastic modulus, wear resistance and good surface quality. The preparation method of the AlTiVCrMoSiN high-entropy alloy nitride coating comprises the step of preparing the AlTiVCrMoSiN high-entropy alloy nitride coating on the surface of a matrix by adopting a cathode arc ion plating deposition method. The preparation method is simple, high in deposition rate and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering materials, and in particular to a high entropy alloy nitride coating and a preparation method thereof and a wear-resistant part. Background Art

[0002] With the continuous development of mechanical manufacturing and energy industries, the performance requirements of key power components in extreme working environments such as high temperature, high pressure and strong friction are increasing. Traditional coating materials often cannot meet the requirements of high hardness and high wear resistance under these harsh conditions. Therefore, it is particularly important to develop new coating materials that can perform excellent performance in extreme environments.

[0003] High entropy alloy nitride coatings, due to their alloy composition of multiple main elements, exhibit excellent mechanical properties and thermal stability, and have become a research hotspot in the field of materials science. In the prior art, the research on high entropy alloy nitride coatings mainly focuses on improving a single performance indicator, such as enhancing the hardness, elastic modulus or wear resistance of the coating by adjusting the alloy composition. However, although existing studies have shown that high entropy alloy nitride coatings exhibit excellent performance in certain fields, there is still no high entropy alloy material that can simultaneously achieve high hardness, high elastic modulus and high wear resistance in the same coating. This has, to a certain extent, limited its wide application in high-end fields such as cutting tools, molds, and aerospace parts. Therefore, the development of high entropy alloy coatings with multiple excellent properties is still one of the important challenges in current materials research.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a high entropy alloy nitride coating and a preparation method thereof and a wear-resistant part to improve the above technical problems.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a high entropy alloy nitride coating, which is an AlTiVCrMoSiN high entropy alloy nitride coating, wherein the element content of Al in the preparation raw material corresponding to the high entropy alloy nitride coating is in the range of 10% to 30%, the element content of Ti is in the range of 10% to 30%, the element content of V is in the range of 10% to 30%, the element content of Cr is in the range of 10% to 30%, the element content of Mo is in the range of 5% to 25%, and the element content of Si is in the range of 1% to 10%.

[0008] In an optional embodiment, the high entropy alloy nitride coating has a thickness of 2 μm to 8 μm.

[0009] In an optional embodiment, the high entropy alloy nitride coating presents a dense and uniform composite form with no obvious characteristic structure and gradually increasing fine grain characteristics from the inside to the outside;

[0010] And / or, the residual stress of the high entropy alloy nitride coating is concentrated in the range of -0.1 GPa to -0.5 GPa;

[0011] And / or, the high entropy alloy nitride coating has a single FCC solid solution structure.

[0012] In a second aspect, the present invention provides a method for preparing a high entropy alloy nitride coating as described in any of the aforementioned embodiments, comprising: using a physical vapor deposition method to deposit the high entropy alloy nitride coating on the surface of a substrate.

[0013] In an optional embodiment, the physical vapor deposition method is a cathode arc ion plating method.

[0014] In an optional embodiment, the conditions of the cathode arc ion plating method include: the reaction gas is nitrogen, the gas pressure is 0.5Pa~3Pa, the nitrogen flow rate is 50sccm~600sccm, the pulse negative bias voltage is ≥100V and ≤300V, the duty cycle is 50%~90%, the target current is 80A~120A, the deposition temperature is 250℃~350℃, and the deposition time is 100min~300min.

[0015] In an optional embodiment, before depositing the high entropy alloy nitride coating, the substrate is subjected to rough grinding, polishing and cleaning in sequence;

[0016] Preferably, the rough grinding is performed by sandpaper of types #180, #500, #800, #1200, #1500, and #2000 in sequence;

[0017] Preferably, the polishing treatment is to mirror-polish the roughly ground substrate with a diamond polishing paste having a particle size of 2 μm to 3 μm and a diamond polishing paste having a particle size of 0.5 μm to 1 μm in sequence. More preferably, the surface roughness of the substrate after the mirror polishing treatment is 20 nm to 500 nm.

[0018] Preferably, the cleaning is ultrasonic cleaning with acetone and anhydrous ethanol in sequence for 15 min to 25 min;

[0019] Preferably, the substrate is titanium alloy or cemented carbide.

[0020] In an optional embodiment, after the cleaning, the substrate is glow cleaned and plasma etched under low vacuum conditions;

[0021] The glow cleaning conditions include: the gas pressure in the furnace is 0.5Pa to 3Pa, the negative bias voltage is 500V to 1000V, the duty cycle is 50% to 90%, the Ar flow rate is 100sccm to 300sccm, the temperature is 250°C to 350°C, and the glow cleaning time is 10min to 30min;

[0022] The conditions of plasma etching include: furnace pressure of 0.5Pa-1.5Pa, negative bias voltage of 600V-1000V, duty cycle of 50%-90%, Ar flow of 100sccm-400sccm, target current of 60A-100A and ion etching time of 10min-20min.

[0023] In a third aspect, the present invention provides a wear-resistant part, which includes a substrate and a high entropy alloy nitride coating as described in any of the aforementioned embodiments deposited on the surface of the substrate.

[0024] In an optional embodiment, the wear-resistant part is a power component, preferably, the wear-resistant part is a blade or a chip cutting tool;

[0025] Preferably, the substrate is titanium alloy or cemented carbide.

[0026] The present invention has the following beneficial effects: the high entropy alloy nitride coating is endowed with excellent comprehensive performance through the synergistic effect of multiple elements, and the high entropy alloy nitride coating has a high ratio of hardness to elastic modulus (H / E), indicating that the coating has good elastic recovery ability, can effectively reduce resistance to external impact, and reduce the generation and expansion of microcracks; the residual compressive stress of the working layer is low, which reduces the risk of coating peeling and cracking due to stress concentration, and improves the bonding force and stability between the coating and the substrate. The wear-resistant parts deposited with the high entropy alloy nitride coating achieve effective modification of the substrate surface and improve the overall performance of the material; the high hardness and excellent mechanical properties of the above-mentioned high entropy alloy nitride coating greatly improve the wear resistance of the substrate, thereby significantly improving the service life and processing efficiency of the wear-resistant parts, and are suitable for applications in high wear environments. In addition, the preparation method of the high entropy alloy nitride coating is simple, the process flow is controllable, the deposition rate is fast, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0028] Figure 1This is a surface scanning electron microscope image of the AlTiVCrMoSiN high entropy alloy nitride coating prepared in Example 1 of the present invention;

[0029] Figure 2 This is a cross-sectional scanning electron microscope image of the AlTiVCrMoSiN high entropy alloy nitride coating prepared in Example 1 of the present invention;

[0030] Figure 3 This is the XRD pattern of the AlTiVCrMoSiN high entropy alloy nitride coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0032] The following is a detailed description of a high entropy alloy nitride coating and a preparation method thereof and a wear-resistant part provided by the present invention.

[0033] Some embodiments of the present invention provide a high entropy alloy nitride coating, which is an AlTiVCrMoSiN high entropy alloy nitride coating, wherein the element content of Al in the preparation raw material corresponding to the high entropy alloy nitride coating is in the range of 10% to 30%, the element content of Ti is in the range of 10% to 30%, the element content of V is in the range of 10% to 30%, the element content of Cr is in the range of 10% to 30%, the element content of Mo is in the range of 5% to 25%, and the element content of Si is in the range of 1% to 10%.

[0034] For reference, the Al content can be 10%, 15%, 20%, 25% or 30%, etc., or any other value within the range of 10% to 30%; the Ti content can be 10%, 15%, 20%, 25% or 30%, etc., or any other value within the range of 10% to 30%; the V content can be 10%, 15%, 20%, 25% or 30%, etc., or any other value within the range of 10% to 30%. The element content of Cr can be 10%, 15%, 20%, 25% or 30%, etc., or any other value within the range of 10% to 30%; the element content of Mo can be 5%, 10%, 15%, 20% or 25%, etc., or any other value within the range of 5% to 25%; the element content of Si can be 1%, 2%, 4%, 6%, 8% or 10%, etc., or any other value within the range of 1% to 10%.

[0035] It should be noted that the high entropy alloy nitride coating is located on the surface of the substrate, which can be a metal substrate or an alloy substrate. The ratio of elements in the above high entropy alloy nitride coating is the ratio of the target element composition during preparation, not the atomic percentage of the elements obtained after deposition. The reason is that due to the different melting points and sputtering yields of the elements in the target, the composition of the deposited coating is somewhat different from that of the original target, among which the Al element content is significantly different from that in the target, and generally speaking, the Al element content in the coating is lower.

[0036] In some embodiments of the present invention, the target material used for deposition may be only AlTiVCrMoSi alloy target, or may be composed of multiple targets including AlTiV alloy target, Cr target and MoSi alloy target. The purity of the above alloy targets is >99.9%.

[0037] It should be noted that the regulation of coating composition mainly depends on the change of Al content. If the Al content is too high, exceeding 30%, a large difference in atomic radius will easily occur in the coating, which will cause obvious lattice distortion in the crystal structure when generating the corresponding ceramic nitride phase, prompting the formation of a hexagonal AlN phase with greater brittleness, and will also produce a multiphase solid solution structure, which will reduce the mechanical properties of the coating and reduce the wear resistance. If the Al content is too low, less than 10%, it may reduce the entropy value in the coating system, which is not conducive to promoting the formation of a stable solid solution structure, and there may be a random arrangement of the atomic structure, and the coating will show an amorphous growth mode, which is easy to cause a loose and porous morphology on the coating surface. This loose and porous structure is more easily destroyed during the friction process, producing a large amount of debris, which will adhere to the friction pair and react on the coating surface, further reducing the wear resistance of the coating.

[0038] In order to make the high entropy alloy nitride coating play a better surface modification role, in some embodiments, the thickness of the high entropy alloy nitride coating is 2μm to 8μm, which can be 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm or 8μm, etc., or any other value within the range of 2μm to 8μm. If the thickness of the AlTiVCrMoSiN high entropy alloy nitride working layer is less than 2μm, it is easy to cause the coating to wear rapidly during the friction process, expose the substrate, and reduce the ability to protect the substrate surface; if the thickness of the AlTiVCrMoSiN high entropy alloy nitride working layer is greater than 8μm, it is easy to cause the residual stress of the coating to accumulate, and the coating is prone to peeling due to excessive surface stress during the deposition process. At the same time, the surface stress concentration during the friction process causes the coating to fail rapidly.

[0039] In some embodiments, the high entropy alloy nitride coating presents a dense and uniform composite form with no obvious feature structure and gradually increasing fine grain characteristics from the inside to the outside; that is, the high entropy alloy nitride coating as a whole presents a dense and uniform growth pattern, wherein this dense and smooth structure exhibits a finer grain size, which can hinder a large number of dislocations and slips at the grain boundaries, so that the coating has excellent mechanical properties such as high hardness and high wear resistance.

[0040] In some embodiments, the surface area of ​​large droplets contained in the high entropy alloy nitride coating is about 8.3% to 25.1% of the total surface area of ​​the coating. The number of large droplets on the surface of the high entropy alloy nitride coating is small and the size is small, the surface is flat, and the surface quality is good. The high entropy effect promotes the stability of a single solid solution structure and a nanocrystalline growth mode, which increases the mobility of atoms to the grain boundary, hinders dislocation and slip at the grain boundary, is conducive to obtaining high hardness and excellent wear resistance, and greatly improves the surface properties of the substrate material.

[0041] In addition, the high entropy alloy nitride coating exhibits a preferred orientation along the (200) crystal plane, showing a single FCC solid solution structure. It also has a high hardness and H / E value, can better achieve substrate surface modification, and improve the service life of the material during wear.

[0042] In some embodiments, the residual stress of the high entropy alloy nitride coating is concentrated in the range of -0.1 GPa to -0.5 GPa, and may be -0.15 GPa, -0.23 GPa, -0.33 GPa, -0.36 GPa or -0.46 GPa.

[0043] In some embodiments, the hardness of the high entropy alloy nitride coating does not exceed 45 GPa, for example, it can be 8.51 GPa to 39.31 GPa, such as 8.51 GPa, 18.07 GPa, 23.95 GPa, 31.19 GPa or 39.99 GPa, or other values ​​within the range of 8.51 GPa to 39.31 GPa; the elastic modulus of the coating does not exceed 426 GPa, for example, it can be 217.60 GPa to 425.77 GPa, such as 234.25 GPa, 217.60 GPa, 279.19 GPa, 324.88 GPa or 425.77 GPa, or other values ​​within the range of 217.60 GPa to 425.77 GPa. The bonding force between the coating and the substrate is not less than 50N, for example, it can be 50N to 70N, such as 50N, 55N, 60N, 65N, 69N or 70N.

[0044] Correspondingly, some embodiments of the present invention also provide a method for preparing a high entropy alloy nitride coating as described in any of the aforementioned embodiments, comprising: using a physical vapor deposition method to deposit the high entropy alloy nitride coating on the surface of a substrate.

[0045] Specifically, in some embodiments, the physical vapor deposition method is a cathode arc ion plating method. Although the cathode arc ion plating method will inevitably produce large droplets on the coating surface, thereby affecting the surface quality of the coating, due to its high ionization rate, the coating has a high deposition rate, and at the same time, microscopic particles with high energy are sputtered, producing a bombardment effect, which enhances the diffusion capacity and nucleation density of the deposited particles; the coating structure obtained by this method is relatively dense and has good mechanical properties. In addition, when preparing the coating, the coating composition can be regulated by reasonably adjusting the size of the arc current on the target surface and introducing a certain nitrogen flow rate to adjust the size of the working gas pressure.

[0046] Furthermore, the deposition process is to continuously obtain a high entropy alloy nitride coating on the surface of the substrate under low vacuum conditions.

[0047] For reference, the above-mentioned high entropy alloy nitride coating can also be specifically made using permanent magnet + controllable pulse electromagnetic composite magnetic field vacuum cathode multi-arc ion plating technology.

[0048] Correspondingly, the conditions of the cathode arc ion plating method include: the reaction gas is nitrogen, the gas pressure is 0.5Pa~8Pa (such as 0.5Pa, 1.0Pa, 1.5Pa, 2.0Pa, 2.5Pa, 3.0Pa, 4.0Pa, 4.5Pa, 5.0Pa, 5.5Pa, 6.0Pa, 6.5Pa, 7.0Pa, 7.5Pa or 8Pa, etc.); the nitrogen flow rate is 100sccm~800sccm (such as 100sccm, 200sccm, 300sccm, 400sccm, 500sccm, 600sccm, 700sccm or 800sccm, etc.); the pulse negative bias voltage is greater than 0V and less than 400V (such as 0.5V, 1V, 5V, 10V, 50V, 100V , 200V, 300V or 400V, etc.); the duty cycle is 50% to 90% (such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.); the target current is 80A to 120A (such as 80A, 85A, 90A, 95A, 100A, 105A, 100A, 115A or 120A, etc.); the deposition temperature is 250℃ to 350℃ (such as 250℃, 270℃, 290℃, 310℃, 330℃ or 350℃, etc.); the deposition time is 100min to 300min (such as 100min, 125min, 150min, 175min, 200min, 225min, 250min, 275min or 300min, etc.).

[0049] It should be noted that in the above process, the bias voltage mainly affects the deposition rate and the density of the core coating; if the bias voltage is too large or too low, the deposition rate will be low and the deposition will be slow. The entropy alloy nitride coating is arc ion plated using a high entropy alloy target under the condition of nitrogen flow. The nitrogen is ionized and forms nitrides with the ionized metal ions. Under the above preparation conditions, metal atoms and nitrogen atoms combine to form a single FCC solid solution structure, which leads to solid solution strengthening of the coating, which is beneficial to increase the hardness and wear resistance of the coating.

[0050] It should be noted that the nitrogen pressure affects the coating structure. If the pressure is too low, the target discharge will be unstable and it will be difficult to form a thin film. If the pressure is too high, it will lead to excessive AlN phase generation, destroying the stable phase structure of the coating, weakening the coating's ability to resist plastic deformation, and reducing wear resistance.

[0051] As mentioned above, the embodiments of the present invention stably control the moving direction and speed of the arc spot on the target surface by reasonably adjusting the nitrogen flow rate, magnetic field electromagnetic voltage and electromagnetic frequency parameters, effectively reducing the size and number of large surface droplets inevitably produced by the arc ion plating process, and optimizing the surface quality of the coating. Affected by the high entropy effect, each element of the prepared coating forms a stable Me-N bond with the nitrogen element, and exists in the entire system in a solid solution manner, forming a stable single solid solution structure. The coating prepared under the above conditions presents a dense and uniform structure without obvious features as a whole. Through the regulation of elemental composition and the adjustment of working parameters, the fine grain characteristics gradually increase. This dense and smooth structure shows a finer grain size, hinders excessive dislocations and slip at the grain boundaries, and makes the coating have excellent mechanical properties such as high hardness and high wear resistance.

[0052] Furthermore, in order to enable the high entropy alloy nitride coating to be deposited on the surface of the substrate and achieve a better deposition effect, the substrate needs to be surface pretreated before deposition.

[0053] For reference, before depositing the high entropy alloy nitride coating, the substrate is subjected to rough grinding, polishing and cleaning in sequence.

[0054] Among them, the coarse grinding is performed by sandpaper of models #180, #500, #800, #1200, #1500, and #2000 in sequence.

[0055] In some embodiments, the polishing process is to mirror-polish the rough-ground substrate with a diamond polishing paste having a particle size of 2 μm to 3 μm (such as 2 μm, 2.5 μm, 3 μm) and a diamond polishing paste having a particle size of 0.5 μm to 1 μm (such as 0.5 μm, 0.8 μm or 1 μm) in sequence. Exemplarily, the surface roughness of the substrate after mirror polishing is 20 nm to 500 nm.

[0056] In some embodiments, ultrasonic cleaning may be used for cleaning, and the ultrasonic cleaning may be performed using acetone and anhydrous ethanol in sequence for 15 min to 25 min.

[0057] Furthermore, the pretreatment also includes: in a low vacuum (pressure less than 5×10 -5 The substrate was glow cleaned and plasma etched under the condition of 0.5447 Pa.

[0058] Among them, the conditions for glow cleaning may include: the gas pressure in the furnace is 0.5Pa~2.5Pa (such as 0.5Pa, 1Pa, 1.5Pa, 2Pa or 2.5Pa, etc.); the negative bias voltage is 500V~1000V (such as 500V, 600V, 700V, 800V, 900V or 1000V, etc.); the Ar flow rate is 100sccm~300sccm (such as 100sccm, 150sccm, 200sccm, 250sccm); cm or 300sccm, etc.); the duty cycle is 50% to 90% (such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.); the temperature is 250°C to 350°C (such as 250°C, 270°C, 290°C, 310°C, 330°C or 350°C, etc.); the glow cleaning time is 10min to 30min (such as 10min, 15min, 20min, 25min or 30min, etc.).

[0059] The conditions for plasma etching may include: a furnace pressure of 0.2Pa to 1.5Pa (such as 0.2Pa, 0.5Pa, 0.8Pa, 1.2Pa or 1.5Pa, etc.); a negative bias voltage of 600V to 1000V (such as 600V, 650V, 700V, 750V, 800V, 850V, 900V, 950V or 1000V, etc.); an Ar flow rate of 100sccm to 300sccm (such as 100sccm, 150sccm, 200sccm, 2 50sccm or 300sccm, etc.); duty cycle is 50% to 90% (such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.); target current is 80A to 120A (such as 80A, 85A, 90A, 95A, 100A, 105A, 100A, 115A or 120A, etc.); ion etching time is 10min to 30min (such as 10min, 15min, 20min, 25min or 30min, etc.).

[0060] It should be noted that the above plasma etching is metal ion etching, wherein Me includes any one of Cr, Ti, and V.

[0061] In some embodiments, the substrate may be titanium alloy or cemented carbide.

[0062] Furthermore, some embodiments of the present invention also provide a wear-resistant part, which includes a substrate and a high entropy alloy nitride coating as described in any of the above embodiments deposited on the surface of the substrate. The parts with the above high entropy alloy nitride coating can have better mechanical properties, hardness and wear resistance. Exemplarily, the wear-resistant part is a power part, specifically, the wear-resistant part can be a blade or a chip cutting tool.

[0063] In some embodiments, there is no transition layer between the high entropy alloy nitride coating and the substrate.

[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0065] Example 1

[0066] This embodiment provides a high entropy alloy nitride coating, which is prepared by the following method:

[0067] (1) The substrate is made of titanium alloy TC4 (Ti-6Al-4V). Before preparation, it is polished with sandpaper of types #180, #500, #800, #1200, #1500, and #2000. The polished substrate is mirror-polished with diamond polishing paste with a particle size of 2.5 μm and diamond polishing paste with a particle size of 1.0 μm until the surface roughness of the substrate is less than 100 nm. After ultrasonic cleaning with acetone and anhydrous ethanol for 20 minutes, it is blown dry with nitrogen gas, and the sample is placed on a plate in the chamber and evacuated to 5.0×10 -3 Pa.

[0068] (2) Before depositing the working layer, the inert gas Ar was introduced to clean the substrate surface. The glow cleaning parameters included: Ar flow rate of 200 sccm, furnace pressure of 2.0 Pa, bias voltage of -900 V, duty cycle of 70%, temperature of 300 °C, and time of 20 min.

[0069] (3) Open the Cr metal target and etch the substrate surface to remove oxides and impurities on the substrate surface and improve the surface activity of the substrate. The arc current is 90A, the gas pressure in the furnace is 0.5Pa, the bias voltage is -900V, the duty cycle is 70%, the Ar flow rate is 200sccm, the electromagnetic voltage is 15V, the temperature is 350℃, and the time is 10min.

[0070] (4) Finally, a high entropy alloy nitride coating, namely AlTiVCrMoSiN high entropy alloy nitride coating, is deposited, the Ar and Cr target currents are turned off, and the baffle is closed to prevent the target from being contaminated. The AlTiVCrMoSiN high entropy alloy nitride coating has an Al content of 20%, a Ti content of 20%, a V content of 20%, a Cr content of 20%, a Mo content of 15%, and a Si content of 5% in the raw materials for preparing the AlTiVCrMoSiN high entropy alloy nitride coating. Nitrogen is introduced with a gas flow rate of 400sccm and a gas pressure of 3.5Pa. The AlTiVCrMoSi alloy target is turned on, and the target current is set to 100A, the temperature to 350℃, the bias voltage to -100V, the duty cycle to 70%, and the deposition time to 120min.

[0071] The surface and cross-sectional scanning electron microscope images of the AlTiVCrMoSiN high entropy alloy nitride coating prepared in Example 1 are shown in FIG. Figure 1 and Figure 2 shown.

[0072] from Figure 1 It can be seen that by counting the number of large droplets on the coating surface, it can be found that the size is small (area <5×10 -2 μm 2 ) and moderate size (18×10 -2 μm 2 ~150×10 -2 μm 2 The number of large droplets in the range of 0.5 to 1.5 μm is the largest, and the large droplets account for 15% of the total area of ​​the coating. The surface roughness of the coating is measured to be 0.257 μm, which has good surface quality.

[0073] from Figure 2 It can be seen that the growth mode of the AlTiVCrMoSiN high entropy alloy nitride coating is dense and uniform, with fine grains, and the total thickness of the coating is measured to be 2.52μm.

[0074] Furthermore, the phase structure of the AlTiVCrMoSiN high entropy alloy nitride coating prepared in this embodiment is as follows: Figure 3 As shown. Figure 3 It can be seen that the AlTiVCrMoSiN high entropy alloy nitride coating presents a preferential growth orientation along the (200) crystal plane, showing a single FCC solid solution structure; the grain size of each plane calculated by XRD spectrum is 8.28nm, showing a nanocrystalline growth mode.

[0075] Example 2

[0076] The difference between this embodiment and embodiment 1 is that during the preparation of the high entropy alloy nitride coating, the bias voltage in the preparation process corresponding to the coating deposited by cathode arc is -200 V. The other preparation conditions are the same as those in embodiment 1.

[0077] Example 3

[0078] The difference between this embodiment and embodiment 1 is that in the process of preparing the high entropy alloy nitride coating, the arc current in the preparation process corresponding to the coating deposited by cathode arc is 300 A. The other preparation conditions are the same as those in embodiment 1.

[0079] Example 4

[0080] The difference between this embodiment and embodiment 1 is that: in the process of preparing the high entropy alloy nitride coating, the element content of Al in the raw material corresponding to the coating deposited by cathode arc is 10%, the element content of Ti is 20%, the element content of V is 20%, the element content of Cr is 20%, the element content of Mo is 25%, and the element content of Si is 5%. The other preparation conditions are the same as those in embodiment 1.

[0081] Example 5

[0082] The difference between this embodiment and embodiment 1 is that: in the process of preparing the high entropy alloy nitride coating, the element content of Al in the raw material corresponding to the coating deposited by cathode arc is 15%, the element content of Ti is 20%, the element content of V is 20%, the element content of Cr is 25%, the element content of Mo is 15%, and the element content of Si is 5%. The other preparation conditions are the same as those in embodiment 1.

[0083] Example 6

[0084] The difference between this embodiment and embodiment 1 is that the base material is YG6 cemented carbide, and in the process of preparing the high entropy alloy nitride coating, the element content of Al in the raw material corresponding to the coating deposited by cathode arc is 25%, the element content of Ti is 15%, the element content of V is 20%, the element content of Cr is 24%, the element content of Mo is 13%, and the element content of Si is 3%. The other preparation conditions are the same as those in embodiment 1.

[0085] Example 7

[0086] The difference between this embodiment and embodiment 1 is that the base material is YG6 cemented carbide, and in the process of preparing the high entropy alloy nitride coating, the element content of Al in the raw material corresponding to the coating deposited by cathode arc is 30%, the element content of Ti is 14%, the element content of V is 20%, the element content of Cr is 24%, the element content of Mo is 10%, and the element content of Si is 2%. The other preparation conditions are the same as those in embodiment 1.

[0087] Comparative Example 1

[0088] The surface hardness of the uncoated TC4 (Ti-6Al-4V) titanium alloy substrate is about 3 GPa and the elastic modulus is 110 GPa.

[0089] Comparative Example 2

[0090] The difference between this comparative example and Example 1 is that the Al content in the raw material corresponding to the high entropy alloy nitride coating is 5%, the Ti content is 20%, the V content is 20%, the Cr content is 20%, the Mo content is 25%, and the Si content is 10%. The other preparation conditions are the same as those in Example 1.

[0091] Comparative Example 3

[0092] The difference between this comparative example and Example 1 is that the Al content in the raw material corresponding to the high entropy alloy nitride coating is 40%, the Ti content is 30%, the V content is 20%, the Cr content is 20%, the Mo content is 15%, and the Si content is 5%. The other preparation conditions are the same as those in Example 1.

[0093] Comparative Example 4

[0094] The difference between this comparative example and Example 1 is that the Al content in the raw material corresponding to the high entropy alloy nitride coating is 5%, the Ti content is 20%, the V content is 20%, the Cr content is 20%, the Mo content is 20%, and the Si content is 15%. The other preparation conditions are the same as those in Example 1.

[0095] Comparative Example 5

[0096] The difference between this comparative example and Example 1 is that the Al content in the raw material corresponding to the high entropy alloy nitride coating is 10%, the Ti content is 40%, the V content is 5%, the Cr content is 10%, the Mo content is 30%, and the Si content is 5%. The other preparation conditions are the same as those in Example 1.

[0097] Comparative Example 6

[0098] The difference between this comparative example and Example 1 is that V, Mo, and Si in the raw materials for preparing the high entropy alloy nitride coating are replaced by Zr and Hf. The other preparation conditions are the same as those in Example 1.

[0099] Comparative Example 7

[0100] The difference between this comparative example and Example 1 is that Mo and Si in the raw materials for preparing the high entropy alloy nitride coating are replaced by Nb. The other preparation conditions are the same as those in Example 1.

[0101] Test example

[0102] The coatings obtained in the above examples and comparative examples were tested and compared in terms of hardness, elastic modulus, and wear resistance.

[0103] The test conditions for the friction coefficient of the high entropy alloy nitride coating are ball-disk friction, rotation speed of 0.2 m / s, load of 5 N, and rotation radius of 8 mm; the calculation formula for the wear rate is W=V / (F×S); where V is the wear amount in mm 3 ; F is the sliding distance, the unit is m; S is the load, the unit is N.

[0104] The results are shown in Table 1.

[0105] Table 1 Performance comparison results

[0106]

[0107]

[0108] It can be seen from Table 1 that the high entropy alloy nitride coating provided by the embodiment of the present invention has high hardness, high elastic modulus and excellent wear resistance, which is beneficial to improving the service life of the corresponding wear-resistant parts.

[0109] In summary, the solution provided by the embodiments of the present invention has at least the following advantages:

[0110] The AlTiVCrMoSiN high entropy alloy nitride coating used is prepared by arc ion plating technology and has excellent hardness and wear resistance. The high-hardness coating can effectively reduce the wear caused by friction between the surface of the base material and the outside world, significantly extend the service life of the base material, and perform well in high-friction and high-temperature working environments. The nitride in the AlTiVCrMoSiN coating has good oxidation resistance and can effectively prevent the reaction between the base material and oxygen in a high-temperature environment, avoiding the degradation of material performance caused by oxidation. At the same time, the coating can maintain stability under high-temperature conditions and effectively improve the high-temperature resistance of the base material. The multi-element design of the AlTiVCrMoSiN high-entropy alloy coating can form a stable solid solution structure through the interaction of elements, thereby effectively improving the mechanical properties, thermal stability and corrosion resistance of the coating. The synergistic effect of multiple elements not only enhances the hardness of the coating, but also improves the adaptability of the coating to the external environment, especially under complex working conditions.

[0111] The arc ion plating process used in the embodiment of the present invention is a mature coating technology with good coating adhesion and uniformity. This technology can achieve high-quality coating deposition, form a solid bond between the coating and the substrate material, and ensure that the coating does not fall off or peel off during use. In addition, the precise control of the coating composition during the arc ion plating process can improve the density of the coating and further enhance its wear resistance and oxidation resistance.

[0112] The materials and preparation processes used in the embodiments of the present invention not only have high performance advantages, but are also relatively environmentally friendly during the production process. Arc ion plating technology reduces the waste of coating materials, which helps to efficiently utilize resources, and the corrosion resistance and wear resistance of the coating increase the service life of the product, thereby helping to reduce the generation of waste and the consumption of resources.

[0113] In summary, the AlTiVCrMoSiN high entropy alloy nitride coating provided by the present invention can effectively improve the service life of the base material, reduce maintenance costs, and show broad application prospects in various industrial fields through its excellent hardness, wear resistance, oxidation resistance, high temperature resistance and the application of arc ion plating technology.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high entropy alloy nitride coating, characterized in that: The high entropy alloy nitride coating is an AlTiVCrMoSiN high entropy alloy nitride coating, wherein the Al element content in the preparation raw material corresponding to the high entropy alloy nitride coating is in the range of 10% to 30%, the Ti element content is in the range of 10% to 30%, the V element content is in the range of 10% to 30%, the Cr element content is in the range of 10% to 30%, the Mo element content is in the range of 5% to 25%, and the Si element content is in the range of 1% to 10%.

2. The high entropy alloy nitride coating according to claim 1, characterized in that: The thickness of the high entropy alloy nitride coating is 2 μm to 8 μm.

3. The high entropy alloy nitride coating according to claim 1, characterized in that: The high entropy alloy nitride coating presents a dense and uniform composite form with no obvious characteristic structure and gradually increasing fine grain characteristics from the inside to the outside; And / or, the residual stress of the high entropy alloy nitride coating is concentrated in the range of -0.1 GPa to -0.5 GPa; And / or, the high entropy alloy nitride coating has a single FCC solid solution structure.

4. A method for preparing a high entropy alloy nitride coating according to any one of claims 1 to 3, characterized in that: It includes: The high entropy alloy nitride coating is formed by depositing it on the surface of the substrate using a physical vapor deposition method.

5. The method for preparing a high entropy alloy nitride coating according to claim 4, characterized in that: The physical vapor deposition method is a cathode arc ion plating method.

6. The method for preparing a high entropy alloy nitride coating according to claim 5, characterized in that: The conditions of the cathode arc ion plating method include: the reaction gas is nitrogen, the gas pressure is 0.5Pa~3Pa, the nitrogen flow rate is 50sccm~600sccm, the pulse negative bias voltage is ≥100V and ≤300V, the duty cycle is 50%~90%, the target current is 80A~120A, the deposition temperature is 250℃~350℃, and the deposition time is 100min~300min.

7. The method for preparing a high entropy alloy nitride coating according to any one of claims 4 to 6, characterized in that: Before depositing the high entropy alloy nitride coating, the substrate is subjected to rough grinding, polishing and cleaning in sequence; Preferably, the rough grinding is performed by sandpaper of types #180, #500, #800, #1200, #1500, and #2000 in sequence; Preferably, the polishing treatment is to mirror-polish the roughly ground substrate with a diamond polishing paste having a particle size of 2 μm to 3 μm and a diamond polishing paste having a particle size of 0.5 μm to 1 μm in sequence. More preferably, the surface roughness of the substrate after the mirror polishing treatment is 20 nm to 500 nm. Preferably, the cleaning is ultrasonic cleaning with acetone and anhydrous ethanol in sequence for 15 min to 25 min; Preferably, the substrate is titanium alloy or cemented carbide.

8. The method for preparing a high entropy alloy nitride coating according to claim 7, characterized in that: After cleaning, the substrate is glow cleaned and plasma etched under low vacuum conditions; The glow cleaning conditions include: the gas pressure in the furnace is 0.5Pa to 3Pa, the negative bias voltage is 500V to 1000V, the duty cycle is 50% to 90%, the Ar flow rate is 100sccm to 300sccm, the temperature is 250°C to 350°C, and the glow cleaning time is 10min to 30min; The conditions of plasma etching include: furnace pressure of 0.5Pa-1.5Pa, negative bias voltage of 600V-1000V, duty cycle of 50%-90%, Ar flow of 100sccm-400sccm, target current of 60A-100A and ion etching time of 10min-20min.

9. A wear-resistant part, characterized in that: The invention comprises a substrate and a high entropy alloy nitride coating as claimed in any one of claims 1 to 3 deposited on the surface of the substrate.

10. The wear-resistant part according to claim 9, characterized in that: The wear-resistant part is a power component, preferably, the wear-resistant part is a blade or a chip cutting tool; Preferably, the substrate is titanium alloy or cemented carbide.